2016
DOI: 10.1038/srep39449
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MEMRI characterization of brain metastases using a 3D Look-Locker T1-mapping sequence

Abstract: Although MEMRI (Manganese Enhanced MRI) informations were obtained on primary tumors in small animals, MEMRI data on metastases are lacking. Thus, our goal was to determine if 3D Look-Locker T1 mapping was an efficient method to evaluate Mn ions transport in brain metastases in vivo. The high spatial resolution in 3D (156 × 156 × 218 μm) of the sequence enabled to detect metastases of 0.3 mm3. In parallel, the T1 quantitation enabled to distinguish three populations of MDA-MB-231 derived brain metastases after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Even though the MP2RAGE TR was set at 6.2 s to maximize the acceleration of the MP2RAGE sequence, it could be lengthened to accommodate for imaging at high magnetic fields. Nonetheless, the T 1 of the mouse brain cortex and metastases measured in vivo were similar to the wide range of values found in the literature and were not modified when applying CS. In the case of very small structures, spatial smoothing can occur and affect the measurements.…”
Section: Discussionsupporting
confidence: 82%
“…Even though the MP2RAGE TR was set at 6.2 s to maximize the acceleration of the MP2RAGE sequence, it could be lengthened to accommodate for imaging at high magnetic fields. Nonetheless, the T 1 of the mouse brain cortex and metastases measured in vivo were similar to the wide range of values found in the literature and were not modified when applying CS. In the case of very small structures, spatial smoothing can occur and affect the measurements.…”
Section: Discussionsupporting
confidence: 82%
“…Fast T 1 mapping of the whole mouse brain with the MS‐MP2RAGE sequence showed the ability to measure T 1 values with low variations along time (less than 1%). The in vivo T 1 values measured with the MS‐MP2RAGE sequence had to be corrected for the inversion efficiency, leading to values within the range found in the existing literature . This study highlights the potential of this sequence to be used during longitudinal studies.…”
Section: Discussionmentioning
confidence: 73%
“…Previous in vitro studies demonstrated the link between CaSR and TRPV6, where TRPV6 action induces calcium ions entry in CaSR [39,40]. The potential leading role of calcium receptors in manganese uptake has also been recently demonstrated by Castets CR et al, in a study where breast or glioma cancer cells lines pre-treated with Mn 2+ and then incubated with calcium blockers enabled to retain Mn 2+ ions into the cells [41].…”
Section: Plos Onementioning
confidence: 76%